Visualization Skills Among Engineering Students Using Problem Based Learning Fogarty Model - Ariffin, Arihasnida; Hamzah, Norhasyimah; Ismail, Mohd Erfy; Samsudin, Mohd Ali; Md. Zain, Ahmad Nurulazam (Journal of Technical Education and Training, 2019)
Engineering Drawing subject’s offered to all students who are enrolled in the civil engineering, electrical engineering or mechanical engineering. These subjects develop skills in geometry drawing more professional. For the concept in Engineering Drawing, students need to have good visualization skills. Visualization is needed to help students get a start before translating into a drawing. To train these skills, a Problem Based Learning (PBL) approach will be implemented. The problem solving process repeatedly attempts to help the student correctly and accurately interpret the drawings of the engineering drawing. The process of learning using PBL method are specifically follow PBL Fogarty Model. This study examined readiness of visualization skills among engineering students through PBL Fogarty Model approach. A total of 68 students of engineering from institutions in Malaysia are involved in this study. The instruments used are Space Ability Test adapted from Bennett, Seashore and Wesman (1972). The findings show that students have a good level of visualization skills. As a result, the more individual a person achieves a good visual cognitive level, the easier it is to master the knowledge, ideas and approaches of the new learning method.